2021
DOI: 10.22270/jddt.v11i5.5021
|View full text |Cite
|
Sign up to set email alerts
|

Laurus nobilis L., (Habb-ul-Ghar), A Review on Phytochemistry, Pharmacology and Ethnomedicinal Uses

Abstract: Habb-ul-Ghar (Laurus nobilis L., fruit) is used in the Unani and other traditional systems of medicine since ancient times. It has been also used in culinary and pharmaceutical industries. Various phytoconstituents were isolated from laurel fruit, like monoterpenes, sesquiterpenes, fatty acids, flavonoids, phenolic acid, and some minerals. Many pharmacological studies have been carried out to explore its anti-oxidant, antimicrobial, antiproliferative, antinociceptive, and anti-inflammatory activities. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In parallel, they prevent the perturbation of plasma electrolyte equilibrium, as shown with the furosemide group (Table 2). Generally, L. nobilis is a natural remedy used in traditional medicine and recommended by numerous traditional healers to treat kidney diseases and digestive system disorders (Usmani et al, 2021). It has been demonstrated that extracts of L. nobilis show a nephroprotective effect in ant treatment at a level of 300 mg/kg for 9 days without altering kidney histological structure (Taroq et al, 2021).…”
Section: Impact Of Daily Administration Of Laurus Nobilis Extract On ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, they prevent the perturbation of plasma electrolyte equilibrium, as shown with the furosemide group (Table 2). Generally, L. nobilis is a natural remedy used in traditional medicine and recommended by numerous traditional healers to treat kidney diseases and digestive system disorders (Usmani et al, 2021). It has been demonstrated that extracts of L. nobilis show a nephroprotective effect in ant treatment at a level of 300 mg/kg for 9 days without altering kidney histological structure (Taroq et al, 2021).…”
Section: Impact Of Daily Administration Of Laurus Nobilis Extract On ...mentioning
confidence: 99%
“…L. nobilis is a small perennial tree and belongs to the Lauraceae family (Nava et al, 2021). This plant is characterized by its aromatic and fragrant effects, and it is used traditionally against a wide range of diseases, including rheumatism, dermatitis, digestive system disorders, and eructation (Usmani et al, 2021). For example, areal and ground parts of L. nobilis are traditionally used in the eastern Mediterranean basin, such as in Türkiye, as diuretic agents (Patrakar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The laurel fruit was used to separate a variety of phytoconstituents, including monoterpenes, sesquiterpenes, fatty acids, flavonoids, phenolic acid, and certain minerals. Its antioxidant, antibacterial, antiproliferative, antinociceptive, and anti-inflammatory effects have been the subject of numerous pharmacological research 68,69 . The Aspartate Aminotransferase (AST), Gamma-Glutamyl Transferase (GGT), and Alanine Aminotransferase (ALT) enzyme levels were significantly reduced, and glucose concentration decreased in Laurus nobilis L. leaf extract on vital organs in streptozotocin-induced diabetic rats 70 .…”
Section: Laurus Nobilis L (Family -Lauraceae)mentioning
confidence: 99%